The Narrow Corner - where homosexuality hides - Furtado, Hélio Dias (Revista Leitura, 2019)
According to his biographers, W. Somerset Maugham was always careful about not allowing traces of his homosexuality to get into his novels. However, it seems Maugham was not entirely successful in carrying out this decision of his. At least, this is what can be concluded after reading Gore Vidal’s Maugham’s Half & Half where he points out The Narrow Corner, Maugham’s novel published in 1932, as one dealing covertly with the homosexuality theme. Our intention is to conduct a careful analysis of this novel to raise its hidden traces of homosexuality which, in Vidal’s view, Maugham is not successful in disguise. DOI: 10.28998/0103-6858.2005v2n36p35-43